Methods to overcome the effects of fluctuation in cement prices to local contractor - Suhaila, Sulong (2010)
Construction sector is one of the largest economy sectors that contributed to the development and prosperous of Malaysia. Cement is a major and essential component of the construction industry in Malaysia. On the average, cement and cement-related products such as cement sand bricks, plasters, concrete roof tiles, reinforced concrete piles, concrete culvert and others comprise fifty percent of the material used in a project. This study is about the methods to overcome the effects of fluctuation in cement prices to local contractor. The selected respondents on this study are contractors, engineers and suppliers in Johor Bahru and Kuala Lumpur. Covering cases were from year 2005 to 2010. All data were analyzed using Microsoft Excel 2003. The result indicated that (50%) methods to overcome the effects of fluctuation in cement prices to local contractor which is introduce more flexible contracting management to accommodate price changes is the most chosen among the respondents.